Tahap Preliminary Research Pengembangan Media Pembelajaran Berbasis Komputer pada Materi Transformasi SMA/MA - Arifa Rahmi; Armiati Armiati; Hendra Syarifuddin (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2021)
The human life aspect’s is concerned with measure activities that geometry context, such as study of plane, space, size and position. Students’ faced the difficulty in understanding concept and interpreting of direction of a transformed geometry object. To solved this difficulty students’ need mathematics learning media which able to clarify transformation context. The aim of this research to know the characteristics and description of mathematics learning media of based computer on geometry transformation context which is should be preliminary research phase. This research was using Plomp model. This model consist to preliminary research phase. This research found that mathematics learning media of based computer on the geometry transformation context was preliminary research phase.